Aplikasi Template Surat Berbasis Web Pada Balai Penerapan Standar Instrumen Lingkungan Hidup Dan Kehutanan Aek Nauli - Bunga Nurul Manisa; Nurmaiyah Nurmaiyah; Abdul Halim Hasugian (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
One of the problems faced by government agencies in BPASILHK Aek Nauli is that the process of writing correspondence is still manual, which has an impact on employees who are less than optimal in writing letters. By utilizing the Microsoft Word application in making letters, it has several main weaknesses, such as dependence on the employee's ability to make letters, which results in the letter format being variable and not as expected by the head office. For this reason, the author created a web-based Letter Template Application at BPSILHK Aek Nauli as a technological solution that facilitates the process of creating, managing and developing letters in this technological era. This application has a variety of features and benefits, including reduced time and effort, increased efficiency, use of standard mail, ease of collaboration, integration with various and reduced costs. With this application, users can easily create various types of letters, such as assignment letters, service letters, orders, permits and so on. Apart from that, this application can also make it easier for users to adjust the letter format according to their needs. Thus, users no longer need to spend a lot of time creating letter documents manually. The web-based letter template application provides convenience and efficiency in the process of preparing letter documents.